Determination of soy proteins in calabresa sausage by densitometry on gel electrophoresis - Paiva, Igor Moura de; Furtado, Marco Antônio Moreira (Instituto Adolfo Lutz Journal - RIAL, 2011)
Soy proteins are widely employed in meat products. However addition of non-meat proteins in calabresa sausages is not allowed according to the Brazilian legislation and in case of the non-declared addition of this foreign protein in consumed food, it may trigger allergic reactions in some consumers. Polyacrylamide gel electrophoresis (SDS-PAGE) was used for determining soy proteins in calabresa sausages. Fraud simulations were performed adding different concentrations (0%; 0.5%; 1%; 2%; 5%; 10%; 20% and 100%) of soy proteins in sausages. The qualitative analysis was not sensitive to detect the lowest concentrations of soy proteins. On the other hand, by using semi-quantitative analysis by means of densitometry of selected protein fractions from soy and porcine meat, the presence of soy proteins could be determined in the all of analyzed concentrations. This methodology could be implemented, without large investments, for conducting quality control of sausages.